2007
DOI: 10.1002/jclp.20407
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of spiritual self‐schema (3‐S+) therapy for reducing impulsivity in HIV‐positive drug users

Abstract: The purpose of this study was twofold. First, pretreatment correlations are presented among impulsivity, intoxicant use, HIV risk behavior, spirituality, and motivation in a sample of 38 HIV-positive drug users. Second, treatment outcomes are presented from a preliminary study of spiritual self-schema (3-S(+)) therapy - a manual-guided psychotherapy integrating cognitive and Buddhist psychologies - for increasing motivation for abstinence, HIV prevention, and medication adherence. Impulsivity was negatively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(76 citation statements)
references
References 50 publications
(51 reference statements)
3
73
0
Order By: Relevance
“…These treatments have been applied to several patient populations, with promising results (Propst et al, 1992;Rosmarin et al, 2010;Harris et al, 2011;Hardman et al, 2003;Margolin et al, 2007, Richards et al, 2006. Even though much of the work on spiritually integrated treatments has grown out of a cognitive-behavioral orientation, practitioners from other therapeutic orientations have also begun to integrate greater spiritual sensitivity into their treatments.…”
Section: Promising Therapeutic Directionsmentioning
confidence: 98%
“…These treatments have been applied to several patient populations, with promising results (Propst et al, 1992;Rosmarin et al, 2010;Harris et al, 2011;Hardman et al, 2003;Margolin et al, 2007, Richards et al, 2006. Even though much of the work on spiritually integrated treatments has grown out of a cognitive-behavioral orientation, practitioners from other therapeutic orientations have also begun to integrate greater spiritual sensitivity into their treatments.…”
Section: Promising Therapeutic Directionsmentioning
confidence: 98%
“…This new schema embodies nonjudgmental reflection, a sense of interconnectedness, inner calm consistent with abstinence, and culminates in the healing of self as well as others (Avants & Margolin, 2004). At the end of treatment clients are referred to a three-tier support system Margolin et al, 2007) in accordance with the Buddhist tradition of ''seeking refuge in the triple gem'' to continue their spiritual development consisting of (1) a spiritual advisor or religious figure of their choosing, (2) lessons in the form of readings, scriptures, and so on, and (3) a fellowship or community of like-minded individuals committed to abstinence and a spiritual code of conduct.…”
Section: Mindfulness-based Treatment Approaches In Addictionmentioning
confidence: 99%
“…Participants are encouraged to view their behavior Bwith compassion, without judgment, and with the goal of targeting and eliminating the addict self-schema, rather than targeting and punishing themselves^(p. 272). Several studies of this treatment have reported reductions in HIV-risk behavior and increases in qualities such as generosity, morality, renunciation, and wisdom (Margolin et al 2006;Margolin et al 2007).…”
Section: Teaching Buddhist-based Ethics In Mbismentioning
confidence: 99%